THE USE OF MOON TEXNOLOGY IN THE INTRODUCTION OF GEOMETRIK SHAPES IN PRESCHOOL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the content of introducing geometric shapes to children of preschool age, the importance of repetition and consolidation of knowledge imparted to children through didactic games